Comparative Evaluation of Healing After Periodontal Flap Surgery Using Silk Sutures and Sutureless Technique:A Split-Mouth Clinical Study - K, Shimreen; Syam, Nita; Ahamed, Shabeer; K, Abhisha; P, Sreeja; PP, Subhna (Journal of Neonatal Surgery, 2025)
Several studies have shown that different surgical periodontal procedures result in distinct healing patterns, making the monitoring of wound healing post-surgery essential. Adhesive materials like cyanoacrylate have appeared as potential alternatives to traditional sutures in periodontal procedures. Aim: This study aims to evaluate tissue-bonding cyanoacrylate with sutures concerning healing and post-surgical risks. Methodology: Ten patients requiring flap surgery (probing depth ≥5mm) were identified. A split-mouth study was adopted, with one side receiving sutures (Group I) and the other cyanoacrylate surgical sealant (Group II). Periodontal probing depth was assessed before surgery and at 6 weeks and 3 months post-surgery. The early healing index (Wachtel et al.) was measured at 1- and 2-weeks post-surgery. Both objective (debris, redness, suture loss) and subjective (discomfort, pain/itching, aesthetics) criteria were recorded. Follow-up visits occurred at 2-, 6 weeks, and 3 months. Results: There were no marked differences observed between the groups about periodontal probing depth (p > 0.05). Both groups showed comparable improvement in subjective and objective parameters after 3 months. However, Group II demonstrated superior healing outcomes, particularly after 6 weeks. Conclusion: Both interventions improved periodontal health, but Group II may offer added benefits in comfort, healing, and patient satisfaction. Additional research involving larger sample sizes is necessary to validate these findings.